Identifying the brightest Galactic globular clusters for future observations by H.E.S.S. and CTA. Issue 1 (11th September 2017) - Ndiyavala, Hambeleleni; Krüger, Petrus Paulus; Venter, Christo
Abstract: We present results from an emission code that assumes millisecond pulsars to be sources of relativistic particles in globular clusters (GCs) and models the resulting spectral energy distribution of Galactic GCs due to these particles' interaction with the cluster magnetic and soft-photon fields. We solve a transport equation for leptons and calculate inverse Compton and synchrotron radiation to make predictions for the flux expected from Galactic GCs. We perform a parameter study and also constrain model parameters for three GCs using γ-ray and X-ray data. We next study the detectability of 16 Galactic GCs for the High Energy Stereoscopic System (H.E.S.S.) and the Cherenkov Telescope Array (CTA), ranking them according to their predicted TeV flux. The spectrum of each cluster and therefore the detectability ranking is very sensitive to the choice of parameters. We expect H.E.S.S. to detect two more GCs (in addition to Terzan 5), i.e. 47 Tucanae and NGC 6388, if these clusters are observed for 100 h. The five most promising GCs for CTA are NGC 6388, 47 Tucanae, Terzan 5, Djorg 2 and Terzan 10. We lastly expect CTA to detect more than half of the known Galactic GC population, depending on observation time and model parameters.